Spiritual Emotional Freedom Technique (SEFT) untuk Menurunkan Stres pada Pasien Hipertensi - Desti Fatmasari; Rahma Widyana; Kondang Budiyani (Jurnal Psikologi, 2019)
This study aims to determine the differences in stress levels in hypertensive patients before and after treatment given SEFT intervention. The design used in this research is one group pretest-posttest design. Subjects in this study were male and female hypertensive patients, aged 40-60 years, had a stress score with moderate to high stress level, minimal junior high school education. Subjects in this study amounted to 5 people. Stress was measured using a stress scale of 28 items. Subjects were treated in the form of SEFT intervention, namely the merging of spirituality (form of prayer and resignation) and psychological energy carried out by three techniques, among others, are set-up, tune-in and tapping. Quantitative data analysis techniques using wilcoxon sign rank analysis is to determine whether there is a difference in stress score between pretest and posttest and posttest and follow up on the subject of research. Analysis of qualitative data from observation, interview, worksheet and evaluation sheet. Based on quantitative results of wilcoxon sign rank test showed that in this study there are significant differences between pretest and posttest with value Z = -2.023ͣ (p <0,050). The results can also be seen from the decrease of mean score between pretest and postest. Pretest with mean score (= 82.20) and posttest with mean value (= 56,20). The posttest average is lower than the pretest average. This means there is a decrease in the score on the pretest average to the posttest. Based on the above explanation can be concluded that the spiritual emotional freedom technique (SEFT) can reduce stress in hypertensive patients. Keywords: Spiritual Emotional Freedom Technique (SEFT), Stress, Hypertension Patient.